Gender Differences in Psychopathy Links to Drug Use - Schulz, Nicole (Law Hum Behav, 2015)
While the relationship between psychopathic personality traits and substance use has received some attention (Hart & Hare, 1989; Smith & Newman, 1990), gender differences have not been thoroughly assessed. The current study examined whether gender modified the relationship between two criminally-relevant constructs, a) psychopathy and its factors and b) drug use. A sample of 318 participants with criminal histories and recent substance use was assessed for psychopathy using the Psychopathy Checklist: Screening Version and for illicit drug use using the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders. As expected, the impulsive-antisocial traits (Factor 2) of psychopathy were positively related to a number of drug use characteristics (symptoms, age of drug initiation, extent of drug experimentation), whereas the interpersonal-affective traits (Factor 1) showed a negative relationship with drug abuse symptoms and a positive relationship with age of first use. In terms of gender differences, analyses revealed that women showed a stronger association between Factor 1 traits and later age of initiation compared to men, and that Factor 2, and antisocial facet in particular, were more strongly related to drug abuse in women than men. These findings suggest that psychopathic traits serve as both protective (Factor 1) and risk (Factor 2) correlates of illicit drug use, and in women, Factor 1 may be especially protective in terms of initiation. These conclusions add to the growing literature on potential routes to substance use and incarceration in women.